(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Cooperative banks in semi-urban and rural areas are increasingly exposed to cyber threats as they adopt digital banking. This study analyzes 400 customer survey responses to assess cyber security preparedness in cooperative banks across Satara, Sangli, and Kolhapur districts. Descriptive statistics reveal that while a majority of customers frequently use digital services and are aware of basic security measures, significant gaps remain in perceived security and communication. For instance, only about half of customers consider internet banking secure, and 14% reported encountering phishing or fraud attempts. Inferential analysis indicates a strong link between user awareness and security outcomes: customers who rated themselves knowledgeable about cyber risks were far less likely to fall victim to fraud (χ²=12.6, p<0.001). A moderate positive correlation was found between cybersecurity knowledge and trust in the bank’s digital security (r=0.29, p<0.05). Regression analysis suggests that proactive customer education by banks is a significant